Mathematics for 3D game programming and computer graphics. - Lengyel, Eric, ....- (Hingham, Massachusetts : Charles River Media, 2002)
1.Vectors 2.Matrices 3.Transforms 4.3D engine geometry 5.Ray tracing 6.Illumination 7.Visibility determination 8.Collision detection 9.Polygonal techniques 10.Linear physics 11.Rotational physics 12.Fluid simulation A.Complex numbers B.Trigonometry reference C.Coordinate systems D.Taylor series E.Answers to exercises
Keywords: Computer graphics; Driedimensionele beeldverwerking; Programmeren; Wiskunde